Factorization methods for photonics and rough surfaces - Lechleiter, Armin (KIT Scientific Publishing, 2008)
This thesis investigates non-destructive testing problems for rough and periodic surfaces, where the task is to determine such structures from scattered waves. Such problems are non-linear and ill-posed. We are interested in the analysis of the Factorization method applied to this class of inverse scattering problems. This method does not attempt to solve a non-linear operator equation for the unknown object but computes a binary criterion characterizing points inside and outside the structure.